IMPLEMENTASI KEBIJAKAN E-TLE DALAM MENINGKATKAN KETERTIBAN LALU LINTAS DAN MENURUNKAN ANGKA KECELAKAAN - Putri, Caesarisca Afriliyanita; Suhifatullah, MI; Darmojo, Hardjito S. (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study is entitled 'Implementation of E-TLE Policy in Improving Traffic Order and Reducing Accident Rates (Case Study: Tangerang City Metro Police)' This study aims to find out the implementation of the E-TLE policy in Tangerang City by using a descriptive qualitative study and a case study approach. The data sources for this study are the Tangerang City Metro Police Traffic Unit, Gakkum Unit, Dakgar Division and also the Tangerang City Community. This research technique was carried out by means of in-depth interviews, observations and documentation studies. This study uses the Van Meter and Van Horn policy implementation theory, with the following results: (1) The standards and objectives of the E-TLE policy are still ineffective, this is because even though standardization has been determined based on regulations and laws, the consistency has not been implemented properly. (2) The resources for the implementation of E-TLE in Tangerang City are considered ineffective because many human resources, namely staff from the Dakgar, have not received training, the budget is still inadequate and there is still a lack of equipment to support the implementation of electronic ticketing in Tangerang City. (3) The organizational characteristics in terms of SOPs are in accordance with applicable regulations and are well implemented by officers, but there are still misinterpretations from the Tangerang City community regarding its implementation. Regarding fragmentation, officials have understood their respective job descriptions and have implemented them, but not all have been able to carry out their roles optimally. (4) Inter-organizational communication has been well established with officials, especially the Tangerang City Metro Police Traffic Unit staff, but in communication with the Tangerang City community, many still do not understand what electronic ticketing is. (5) The disposition (nature of the implementers) in implementing electronic ticketing is quite cooperative and also helps the Tangerang City community in confirming electronic ticketing. (6) The social and economic conditions of the Tangerang City community greatly influence the implementation of the E-TLE policy in Tangerang City. Many people still have not accepted the existence of electronic ticketing and feel indifferent to traffic order. Regarding the economic environment, it is very influential for affected communities, especially those with low incomes. In addition, it has an impact on regional income because traffic ticket fines are included in the PNPB. Keywords: Policy Implementation, E-TLE, Tangerang City